Human Rights-Based Community Practice in the United States - Libal, Kathryn R.; Harding, Scott (SpringerBriefs in Rights-Based Approaches to Social Work, 2015)
A transformative model for community social work rooted in basic social and economic rights is the basis of this timely Brief. With specific chapters spotlighting the rights to health care, nutritious food, and adequate and affordable housing, the book describes in depth the role of community practice in securing rights for underserved and vulnerable groups and models key aspects of rights-based work such as empowerment, participation, and collaboration. Case examples relate local struggles to larger regional and statewide campaigns, illustrating ways the book's framework can inform policymakers and improve social structures in the larger community. This rights-based perspective contrasts sharply with the deficits-based approach commonly employed in community social work, and has the potential to inspire new strategies for addressing systemic social inequality. Features of Human Rights-Based Community Practice in the United States: A conceptual basis for a rights-based approach to community practice. Detailed analysis of legal and social barriers to health care, housing, and food. Examples of effective and emerging rights-based community interventions. Methods for assessing the state of human rights at the community level. Documents, discussion questions, resource lists, and other valuable tools. .